Tindak Tutur Ilokusi Ekspresif dan Direktif dalam Komik “Witch Hunt” Berbasis Webtoon Karya Sso Park ( Kajian Pragmatik) - Rizky Ananda Putri; Hanafi Hanafi (Departement of Mathematics Education, 2024)
This research has the main purpose to classify and explain the various forms of illocutionary speech acts, both expressive and directive, contained in the comic entitled